Pengaruh Kemampuan Awal dan Motivasi Belajar Terhadap Kemampuan Kognitif Siswa Pada Mata Pelajaran Pai Di SMA Negeri 2 Masohi - Nurma Yunita Peu’uma (Peneliti.net, 2019)
This research was aimed to investigate; (1) the influence of initial ability towards students’ cognitive ability at SMA Negeri 2 Masohi; (2) the influence of learning motivation towards students’ cognitive ability at SMA Negeri 2 Masohi; (3) the influence of initial ability towards students learning motivation at SMA Negeri 2 Masohi. This study was a quantitative research, within 229 students at eleventh grade as the population, and 58 students as the sample chosen by using random sampling technique. The data collection used in this research was test and questioner. The data analysis used in this research was descriptive analysis and inferential. The research hypothesis test was path analysis. The result of the research showed that (1) there was a direct influence of initial ability towards students’cognitive ability at SMA Negeri 2 Masohi; (2) there was direct influence of learning motivation towards students’cognitive ability at SMA Negeri 2 Masohi; (3) there was direct influence of initial ability towards students’ learning motivation at SMA Negeri 2 Masohi. Therefore, students’ cognitive ability could be improved with students’ initial ability in mastering prior subject.Students’ cognitive ability could also be improved with the high learning motivation of students in improving their knowledge. Students’ learning motivation could be improved with initial ability in mastering a relevance subject with the upcoming learning material.